Desert Spread and Desertification - Some Basic Issues - Singh, Surendra (Annals of Arid Zone, 2025)
Significant variations detected from the multidate and multispectral satellite images and ground truth on the climatological, physical and biological resources have conclusively proved that the Indian desert is not spreading towards east and northeast. Contrary to it, tlie fortiler li iiit of the desert was more extensive and wide-spread and the desert has shrunk to the west. However, due to i icreasirig human activities and climatic fluctuations in the last few decades, the desertificatiotl processes like wind erosion/deposition, water erosion, salinity/ alkalinityand vegetation degradation have depleted tlie biological productivity o f four major latiduse syste ilso f tlie Indian desert. Thus, the desert spread and desertification are two diKerent problem.